The Coherence of Smoking Behavior Towards Acute Respiratory Infection Cases in Toddlers - Sharfina, Dirayati; Fauziah (Talenta Publisher, 2021)
Preschool children have weak and imperfect immunity systems making them prone to ARI (Acute Respiratory Infection) diseases. One of the causes is family's member smoking behaviour which causes the number of ARI cases in preschool children. This research aims to determine the coherence of family members' smoking behaviour towards ARIs cases in children aged 3-5 years old. It used a cross-sectional study design and purposive sampling techniques with 34 children. The population of this study is the preschool children within the working area of Kampung Baru Community Health Center, Tanjung Balai city. The research results showed that the smoking behaviour of the family members is categorized as heavy smokers. The ARI cases showed that most children prone to the ARI diseases. Also, the significant coherence of family members' smoking behaviour towards ARI cases in children aged 3-5 years old showed a value of p - 0.0001 < a = 0.05. This research suggests that the Kampung Baru Community Health Center should keep providing health education and socialize the family to not smoke around the children to prevent ARI cases to them.